Comparative effectiveness of statins and exercise in high-risk individuals: systematic review and network meta-analysis - Chen, Jia-Li; Zhang, Jin-Tao; Li, Xue-Hui; Wu, Ruo-Shan; Ma, Hong-Tao (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsArterial stiffness (AS) predicts cardiovascular disease (CVD) risk and relates to multiple factors. But the best interventions for AS in high—risk CVD groups are unknown. This review focuses on how different interventions affect AS and related indicators.MethodsWe searched MEDLINE (PubMed), Embase, Cochrane Library, EBSCO, and Web of Science for relevant studies. Inclusion criteria: (1) randomized controlled trials (RCT); (2) participants with CVD risk factors as per American College of Sports Medicine (ACSM) guidelines; (3) interventions including Whole-Body Vibration (WBV), statins (STA), interval training (INT), aerobic exercise (AE), resistance exercise (RT), and combined exercise (CT); (4) control groups with usual care or placebo; (5) outcomes of pulse wave velocity (PWV), systolic blood pressure (SBP), and diastolic blood pressure (DBP); (6) studies in English. Data were analyzed using a random effects network meta-analysis and assessed for bias using the Cochrane tool.ResultsThis meta-analysis of 58 studies (n = 2,931) found all long-term interventions (STA, WBV, CT, RT, AE, INT) significantly reduced PWV (p < 0.001). WBV, INT, and AE notably lowered both SBP and DBP (p < 0.001). hSTA showed optimal PWV reduction (SUCRA=92.0), while WBV showed highest efficacy for SBP (SUCRA=94.0) and DBP (SUCRA=77.3).ConclusionsFor CVD high-risk populations, high doses of statins (hSTA) optimally reduces AS; WBV is the top non-drug AS intervention, while INT best improves both AS and BP short-term. Combined, these interventions significantly enhance outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=564538, PROSPERO CRD42024564538.